Role of the Vitamin K Epoxide Reductase Complex Subunit 1 (VKORC1) −1639G>A Gene Polymorphism in Patients with Retinal Vein Occlusion. (December 2013) - Weger, Martin; Steinbrugger, Iris; Renner, Wilfried; Pöschl, Eva Maria; Brockmann, Tobias; Rabensteiner, Dieter Franz; El-Shabrawi, Yosuf; Haas, Anton
Abstract Purpose of the study: Retinal vein occlusion (RVO) is a major vision-threatening disease. Vitamin K epoxide reductase recycles reduced vitamin K, which is essential for the gamma carboxylation of clotting factors II, VII, IX, X and proteins C and S. Recently, the vitamin K epoxide reductase complex subunit 1 (VKORC1) −1639G>A (rs9923231) polymorphism has been reported as a novel risk factor for RVO in a Turkish population. The present study was set to confirm or to refute this association in a larger cohort of patients with RVO. Materials and methods: The present case–control study comprised 285 patients with central RVO, 401 patients with branch RVO and 333 control subjects. Genotypes of the VKORC1 −1639G>A polymorphism were determined by 5′ exonuclease assay (TaqMan). Results: No significant differences in either genotype distributions or allele frequencies of the vitamin K epoxide reductase complex subunit 1 −1639G>A polymorphism were found between patients and control subjects (p > 0.05). In a logistic regression analysis neither branch nor central RVO was predicted by the vitamin K epoxide reductase complex subunit 1 −1639G>A genotypes, but by arterial hypertension, ever-smoking status and in case of central RVO additionally by diabetes mellitus. Conclusions: Our data suggest that the vitamin K epoxide reductase complex subunit 1 −1639G>A gene polymorphism is unlikely a major risk factor for patients with either central or branch RVO.